2008
DOI: 10.4017/gt.2008.07.02.172.00
|View full text |Cite
|
Sign up to set email alerts
|

Social and physiological influences of living with seal robots in an elderly care house for two months

Abstract: Robot therapy for elderly residents in a care house has been conducted since June 2005. Two therapeutic seal robots were introduced and activated for over 9 hours every day to interact with the residents. This paper presents a progress report of this experiment. In order to investigate the psychological and social effects of the robots, each subject was interviewed by using the free pile sort method, and their social interaction was analysed. In addition, their hormones in urine: 17 -Ketosteroid sulfate (17-KS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Robots indeed play a vital role in helping the elderly [18]. For example, the seal robot Paro developed in Japan was developed to meet the psychological and companionship needs of the elderly in hospitals, especially those with dementia [19,20]. Robots can assist the elderly in preparing meals [21], lifting heavy objects [22], offering companionship [23], facilitating social interaction [24], and serving as therapeutic tools [19].…”
Section: Robot Assistance To the Elderlymentioning
confidence: 99%
“…Robots indeed play a vital role in helping the elderly [18]. For example, the seal robot Paro developed in Japan was developed to meet the psychological and companionship needs of the elderly in hospitals, especially those with dementia [19,20]. Robots can assist the elderly in preparing meals [21], lifting heavy objects [22], offering companionship [23], facilitating social interaction [24], and serving as therapeutic tools [19].…”
Section: Robot Assistance To the Elderlymentioning
confidence: 99%
“…For example, PARO is very friendly because of its soft visual aspect that looks like a pet. Using PARO robot in an elderly care house, Wada and Shibata found that elderly's stress reaction decreased by interactions with PARO [1], and PARO encouraged them to communicate with each other [2]. Human-robot communication is also an important component for an affinity, as we can see with Aldebaran's Pepper robot [3].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on the adaptation of information communication technology (ICT) to assist older people have proven it to be effective in curbing loneliness [ 10 ], wandering [ 11 ], anxiety, and depression [ 12 ]. Several robots have been developed and reported to influence older people’s cognitive function [ 13 , 14 ], physiological factors [ 15 , 16 ], behavioral and psychological symptoms of dementia (BPSD) [ 17 ], and relationships with their surroundings [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the limited adoption of robots in actual settings can be attributed to the lack of demonstrated effects [ 24 , 25 ]. Most studies were conducted in hospitals, nursing homes, care facilities, and living lab settings [ 14 , 15 , 16 , 17 , 26 , 27 , 28 ]. Abdi et al [ 29 ] pointed out that future studies on robot assistants should be more conscious of real-life scenarios.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation